Multi-walled carbon nanotubes/woven kenaf fabric-reinforced epoxy laminated composites - Nurul Hidayah Ismail; Mohd Hafizi Mohamad; Mariatti Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was carried out to investigate the effect of adding 1 vol% of multi-walled carbon nanotubes (MWCNT) into woven kenaf/epoxy laminated composites on their flexural properties and to compare between two techniques used to incorporate MWCNT into the composite which are spraying and solution techniques. Furthermore, the effect of MWCNT addition in woven glass/woven kenaf/epoxy hybrid composites at the same filler concentration on the flexural properties were also investigated. All the laminated composites with and without MWCNT were fabricated using vacuum bagging method. The flexural properties of the composite samples with and without MWCNT were evaluated by applying three-point bending test. The results were supported by morphological observation. It was found that the addition of MWCNT using both spraying and solution techniques reduced the flexural strength and flexural modulus of MWCNT/woven kenaf/epoxy composites, with obvious reduction trend was shown by former technique. The morphological observation of the composites fracture surface showed that delamination failure occurred in MWCNT/woven kenaf/epoxy laminated composite prepared by spraying technique. Further investigation on hybrid composites showed that MWCNT/woven glass/woven kenaf/epoxy laminated hybrid composites exhibited significant improvement in the flexural properties.